Juvenile Idiopathic Stabbing Headache - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
A series of 83 juvenile patients with idiopathic stabbing headache, 3.3% of all juvenile patients referred because of recurrent headache, is reported from the Paediatric Neurology Services of the University of Ferrara and the University of Padua, Italy.